Ancylocoelium typicum (Trematoda, Monorchiidae) — паразит ставрид рода Trachurus - Гаевская, А.В. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2003)
Уточнены детали морфологического строения и меристических признаков трематоды Ancylocoelium typicum Nicoll, 1912. Материал получен от 4 видов ставрид рода Trachurus, отловленных от Бискайского залива до вод юго-западной Африки. The morphological and measurements characters of the trematode Ancylo-coelium typicum Nicoll, 1912 are redescribed in details. The material was obtained from four horse-mackerel species caught in the Atlantic Ocean from the Biscay Bay to the south-western coast of Africa.